Bridging Language Pedagogy and Indian Philosophical Insights: An Analytical Exploration - Singh, Amrendra K; Majhi, Tulasi Das (Journal of Education Culture and Society, 2025)
Aim. Contrary to other philosophical paradigms, language, according to Indian philosophical traditions such as Vedanta, Nyaya, and Mimamsa, becomes a very complex set of human affairs in which we find existence, reality, and meaning, through which we may realize the nature of both human beings and existence around them. Methods. The Upanishadic traditions of dialogue on existential inquiry; the precision of Sanskrit in denoting abstract concepts; and the pedagogy of the Gurukula system that creates an immersive environment for textual engagement in which the close interaction of students with their gurus fosters language engagement and the talk of spiritual and philosophical matters through modeling are examined. Results. Language teaching, rather than just an act of teaching how to speak, became an act of exciting spiritual and philosophical investigation in pedagogy. On the one hand, the structural complexity of Sanskrit was an aid to the nuanced expression of metaphysical ideas. On the other hypothesis, the Gurukula environment fostered a culture of oral interaction and engagement with texts. The dialogue methods of the Upanishads further supported the notion that learning occurs through communal inquiry and incorporates cognitive, linguistic, and ethical development. Conclusions. Thus, within this philosophical framework, language serves as a bridge between human communication and cosmic truth. In consonance with the rigor of Sanskrit and with dialogic learning and an all-encompassing pedagogy, these traditions fostered language proficiency and metaphysical insight. This integrative approach, where the interdependent nature of language, thought, and being is deemed essential, provides a paradigm for contemporary education where critical thinking and interdisciplinary understanding take precedence. In this connection, the relevance of this study lies in establishing the importance of India’s philosophical-linguistic synthesis in training our thinking towards diversified modern paradigms of pedagogy.